The devastating effects of money laundering on a nation’s socio economy: a case study of Malaysia - Azman, Izza Maryam; Zul Kepli, Mohd Yazid; Puniran, Mohd Noor Ikram (2018)
This article highlights the adverse consequences of corruption and money laundering and its crippling effect on the nation’s economy with special attention to the Malaysian landscape. This article argues that the effects are worse than previously predicted. The devastating effects include political instability, economic instability and digression, loss of control over economic policy, loss of reputation, loss of competitiveness, productivity and investment, loss of government revenue and privatization efforts. In addition, money laundering encourages crimes and reduces people’s lifestyle and quality of life. The main references for this article include analysis reports prepared by regulators, articles in established journals, newspaper reports and interviews with academicians and leading experts.